A Criminological Review on ʽCornering the Marketʽ Practice in Securities Trading in Capital Market (a Study in Indonesia) - SUFM, Dasco Ahmad; Aldyan, Arsyad; Pujiyono, Pujiyono (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505/jarle.v8.7(29).26, 2017)
This article regards criminological study on ʽcornering the marketʽ practice in securities trading in capital market. Cornering the Market can be considered as creating a pseudo or misleading representation because when the actors do their action creates a representation that securities trading seems to be active and to increase dramatically, viewed from the condition of trading volume market, leading to the increase in the price of securities due to purchasing in large volume and eventually resulting in the decrease due to selling in large volume by the actors of Cornering the Market. In Indonesia, Cornering the Market practice is a crime, the manipulation crime in securities trade. It breaks the provision of Articles 91 and 92 of Republic of Indonesia’s Law Number 8 of 1995 about Capital Market and Article II.9 of Regulation Number II-A about Equity Stock Trading. Considering the provision of Article 104 of Law Number 8 of 1995 about Capital Market, Cornering the Market practice can be threatened with 10-years imprisonment and fine of IDR 15.000.000.000,00 (fifteen billions rupiah).